Relationship Between Mother's Knowledge Level In Utilizing The Maternal and Child Health Book With The Nutritional Status Of Toddlers - Fauziah Ikhsanina Shiyam; Bau Kanang; Nur Al-Faida (International Journal of Public Health, 2024)
The Maternal and Child Health (MCH) book is an initiative by the Indonesian Ministry of Health aimed at addressing child nutrition problems. However, at the Karang Mulia Health Center UPTD, the distribution and utilization of the MCH book among mothers of toddlers have not met the national target. The area has reported 164 cases of undernutrition and 74 cases of overnutrition in children under five. This study aims to determine the relationship between the level of maternal knowledge in utilizing the MCH book and the nutritional status of toddlers aged 12-59 months in the working area of the Karang Mulia Health Center UPTD. This correlational analytic research used a cross-sectional approach. The study population included 640 toddlers, with 90 selected samples of mothers who had the MCH book. Purposive sampling was employed, and data were analyzed using the Statistical Program for Social Science (SPSS) version 16.0, applying the chi-square test. The study found no significant relationship between maternal knowledge in using the MCH book and the nutritional status of toddlers. The p-values for the BB/A, PB/A or TB/A, and BB/PB or BB/TB indices were 0.345, 0.851, and 0.282, respectively, all greater than 0.05. There is no significant relationship between maternal knowledge of the MCH book and the nutritional status of toddlers aged 12-59 months in the Karang Mulia Health Center UPTD.